Objective assessment of attention‐deficit/hyperactivity disorder in older adults compared with controls using the QbTest. (5th July 2019) - Bijlenga, Denise; Ulberstad, Fredrik; Thorell, Lisa B.; Christiansen, Hanna; Hirsch, Oliver; Kooij, J.J. Sandra
Abstract : Objectives: Attention‐deficit/hyperactivity disorder (ADHD) persists into old age, with prevalence rates of 2.8% to 3.3% in adults over 60 years of age. Most diagnostic assessment tools are not validated for older adults. The Quantified behavioral Test (QbTest) is an objective assessment for the core symptoms of ADHD and is validated for children and younger adults. We investigated whether the QbTest can be used to differentiate between older adults with ADHD and healthy controls. Methods: Older adults aged 55 to 79 years with (n = 97) or without (n = 112) ADHD were assessed with the QbTest. They also rated their ADHD symptom severity. QbTest raw scores were compared between groups. Factor scores were computed using factor loadings from a confirmatory factor analysis (CFA). Multilevel regressions were used to determine effects of background characteristics and comorbidity. Logistic regressions were performed to determine whether the QbTest differentiated between patients with ADHD and healthy controls. Results: The factor structure of the CFA was comparable with that of younger age groups. Older age was associated with higher Inattention score. Parameters comprising the factors Hyperactivity and Inattention, but not Impulsivity, were shown to contribute significantly in differentiating between the groups. The QbTest had a correct classification rate of 70%, which was increased to 91% when combining QbTest scores and self‐reports of ADHD symptom severity. Conclusions: The QbTest is feasible for older adults, and the factors Hyperactivity and Inattention are valid parameters for the diagnostic assessment of ADHD in older adults, when used in addition to self‐reports.